Isolasi dan Kolonisasi Mikoriza Vesikula Arbuskular (MVA) pada Perakaranan Tanaman Jagung (Zea mays L.) di Lahan Kering Kabupaten Timor Tengah Utara - Fallo, Gergonius (Fakultas Pertanian, Sains, dan Kesehatan, Universitas Timor, 2024)
North Central Timor (TTU) Regency has adry land area for agriculture of 184,421 Ha. Unfortunately, the dry land is known to have low soil fertility. One of alternatives to overcome this problem is to utilize a fungus that has mutualism symbiosis with plant roots, namely vesicular arbuscular mycorrhiza (VAM).This study aims to discover spore character and VAM type, as well as discover the percentage level of VAM colonization on maize roots (Zea mays L.). Samples of soil and maize roots were taken from Fatuneno Village and Bitefa Village using the stratified random sampling method. The isolation of VAM spores was conductedthrough stratified screening method. The microscopic characteristics of the spores were matched with the identification guidelines on the INVAM.com website. Root colonization was seen based on the percentage of root infection by the VAM structure. The results showed that the number of VAM spores per 100 grams of soil from Fatuneno Village was 247 spores and from Bitefa Village was 209 spores. Identification results generated three types of VAM genus, namely Glomus, Acaulospora and Gigaspora. The observations of VAM colonization on the maize roots from Fatuneno Village when the maize was 2 weeks old showed the percentage of 50% with medium category, and when the maize was 4 weeks old the percentage of colonization was 73.3% with high category. In Bitefa Village, the percentage of VAM colonization in maize of 2weeks old was 25% with low category, while when it was 4 weeks old, the percentage of VAM colonization was 33% with medium category.